Relationship of Pancreatic Volumes Using CT Scan in Indonesian Adults with Age, Sex, and Body Mass Index - Mu'ti, Abdul; Paramita, Swandari (Folia Medica Indonesiana, 2020)
The volume of internal organs, including pancreas, show potential health problems. Several medical conditions are associated with the volume of the pancreas. The study aimed to determine the pancreatic volumes using a computed tomography (CT) scan in normal Indonesian adults and to determine whether the age, sex, and body mass index (BMI) influence the measurement of pancreatic volumes. The study was conducted by 119 people aged between 20-77 years old. Pancreatic volume measurement was performed using the summation of area technique. Statistical analyzes used independent t-test and Pearson correlation test. The study showed a significant difference of pancreatic volumes between normoweight and overweight individuals with p=0.041 (p<0.05). The results showed a significant difference of pancreatic volumes between male and female with p=0.020 (p<0.05). The results showed a significant correlation between pancreatic volumes and age p=0.004 (p<0.05). These findings suggest that the change in pancreas volume with age, sex, and BMI is comparable among different ethnicities, which is also in line with other studies.